1970
DOI: 10.3126/njog.v5i1.5055
|View full text |Cite
|
Sign up to set email alerts
|

Mass Hysteria and Adolescent Girl: An Interventional Study

Abstract: DOI: http://dx.doi.org/10.3126/njog.v5i1.5055 NJOG 2010 Jul-Aug; 5(1): 17-20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…We have few published studies on mass hysteria in children from Nepal till date. [ 4 5 ] Our report is significantly different from other reported outbreaks in that there were recurrent episodes of “mass hysteria” in the same school over the period of 3 consecutive years. We concluded the study findings as being a special case of “recurrent epidemic of mass hysteria.” Our study differed from other published studies in that we did not find any specific precipitating factors associated with the onset of the outbreak, which has been routinely mentioned in the available literature.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…We have few published studies on mass hysteria in children from Nepal till date. [ 4 5 ] Our report is significantly different from other reported outbreaks in that there were recurrent episodes of “mass hysteria” in the same school over the period of 3 consecutive years. We concluded the study findings as being a special case of “recurrent epidemic of mass hysteria.” Our study differed from other published studies in that we did not find any specific precipitating factors associated with the onset of the outbreak, which has been routinely mentioned in the available literature.…”
Section: Discussioncontrasting
confidence: 82%
“…The same has been reported by other authors from Nepal. [ 4 5 9 ] Available literature on mass hysteria in children showed that younger girls were more susceptible, but disturbance was more severe and lasted longer in older girls. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were differences between male and female children in the way they expressed the traumatic event, which is perhaps attributable to the Islam culture and the patriarchal family system in their home: Boys reproduced their stories directly in the sandtray, whereas girls represented their stories indirectly, in the form of an attack from a tiger or a snake. This suggests the need for a future study on how cultural factors may influence the way refugee children express their traumatic experience in sandplay therapy (Jang, 2017;Maharatta et al, 2017;Sharma et al, 2010). Through sandplay, participants were able to SeHwa Lee․Mikyung Jang / A Study of Themes and Symbols in Group Sandplay Therapy of Rohingya Refugee Children in Malaysia…”
Section: ⅳ Conclusionmentioning
confidence: 99%
“…This study demonstrates that sandplay therapy is a suitable method of psychotherapeutic intervention in a culture that regards expressing feelings in nonverbal ways as more appropriate than to verbalize them. Furthermore, given that the culture of Nepal is strongly influenced by Hinduism and at the same time it has a patriarchal society, the way in which women and men express themselves is different (Maharatta et al, 2017;Sharma et al, 2010). These differences require further study.…”
Section: ⅲ Conclusionmentioning
confidence: 99%